2023
DOI: 10.1002/jcaf.22621
|View full text |Cite
|
Sign up to set email alerts
|

Early evidence of the effect of ASU 2017‐12 on derivative disclosure compliance

Abstract: The growth in the use of financial derivatives for a variety of purposes has caused increased complexity in derivative reporting standards. As such, financial statement users have asked the Financial Accounting Standards Board to update guidance to increase transparency while preparers seek clearer guidance on the application of standards and a broadened scope of hedge accounting. The most recent derivative accounting guidance update, ASU 2017‐12 (Topic 815), broadens instruments that qualify for hedge account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Recent studies have found that SFAS 161 disclosures resulted in less asymmetry of information for investors (Steffen, 2022), an increase in stock liquidity (Chen, Dou, & Zou, 2021), and a better user understanding of the effects of derivative and hedging operations on future firm performance, and less mispricing by investors (Campbell, Khan, & Pierce, 2021). Troyer, Johnston, and Trimble (2023) find that derivative disclosure practices decreased after the implementation of ASU 2017-12 (Topic 815). This standard update aims to better align hedge accounting with an organization's risk management activities in terms of its financial statements.…”
Section: Hedge Accounting Researchmentioning
confidence: 96%
“…Recent studies have found that SFAS 161 disclosures resulted in less asymmetry of information for investors (Steffen, 2022), an increase in stock liquidity (Chen, Dou, & Zou, 2021), and a better user understanding of the effects of derivative and hedging operations on future firm performance, and less mispricing by investors (Campbell, Khan, & Pierce, 2021). Troyer, Johnston, and Trimble (2023) find that derivative disclosure practices decreased after the implementation of ASU 2017-12 (Topic 815). This standard update aims to better align hedge accounting with an organization's risk management activities in terms of its financial statements.…”
Section: Hedge Accounting Researchmentioning
confidence: 96%